The antihyperlipidemic effect of a combined supplement of standardized dry extracts of amla (Emblica officinalis), walnut (Juglans regia), olive (Olea europaea) and red yeast rice (Monascus purpureus) powder: Reduction in circulatory low-density lipoprotein-cholesterol (LDL-C) and remnant cholesterol (RC) levels in patients with hypercholesterolemia - Hermans, Michel P.; Dierckxsens, Yvan; Janssens, Isabelle; Seidel, Laurence; Albert, Adelin; Ahn, Sylvie A.; Rousseau, Michel F.; Khan, Amjad (Frontiers in Pharmacology, 2023)
Background: Hyperlipidemia is associated with a higher rate of cardiovascular, cerebrovascular, and peripheral vascular disease. Conventional drugs such as statins are effective in controlling hyperlipidemia; however, they are associated with various side effects, especially myalgia. Nutraceutical lipid-lowering interventions are becoming increasingly popular, particularly among patients who are intolerant or refractory to statins. Substantial preclinical and clinical evidence suggests that extracts of amla, walnut, and olive, and red yeast rice (RYR) powder possess significant antihyperlipidemic effects. Aims: This study aimed to evaluate the efficacy, safety, and patient satisfaction of a combined supplementation of standardized dry extracts of amla fruit (500 mg), walnut leaves (50 mg), olive fruit (25 mg), and RYR powder (33.6 mg) (Cholesfytol NG®) in hypercholesterolemic patients. Methods: This was a real-life setting, retrospective, observational, single-arm, non-randomized study in hypercholesterolemic patients (total cholesterol (TC) ≥ 200 mg/dL or low-density lipoprotein-cholesterol (LDL-C) ≥ 130 mg/dL), enrolled at 57 general practitioner (GP) surgeries in Belgium from March 2020 to January 2022. These patients received a GP-prescribed daily single dosage of two oral tablets of Cholesfytol NG® supplementation for 2 months to overcome their hypercholesterolemia in the absence of a conventional lipid-lowering drug (n = 208) or with a lipid-lowering drug (n = 13). At 2-month follow-up, the lipid profile was re-evaluated, alongside a patient’s questionnaire on treatment general satisfaction and willingness to pursue supplementation. Results: After supplementation, TC decreased by 15%, LDL-C by 19%, non-high-density lipoprotein-cholesterol (non-HDL-C) by 20% (all p < 0.0001), triglycerides (TG) by 9% (p = 0.0028) (−18.4%, p = 0.0042, in patients with baseline TG > 180 mg/dL, n = 58), and remnant cholesterol (RC) by 12% (p = 0.0001). These changes were unaffected by statin intolerance status in patients who received Cholesfytol NG® alongside statin. The supplement was well tolerated by all patients, and no serious adverse events or supplement-emergent effects were reported. Most patients were satisfied with the supplementation and wanted to pursue the nutraceutical. Conclusion: According to the results of this study, a combined supplementation of amla, walnut, and olive extracts, and RYR powder exerts a significant antihyperlipidemic effect, leading to a decrease in circulatory LDL-C and RC levels in patients with hypercholesterolemia. The supplementation bears excellent safety and tolerability, and is rated as satisfactory and pursuable, even among patients with statin intolerance. Clinical Trial Registration: clinicaltrials.gov; identifier number: NCT06002893